The Traditional Games of Macabebe, Pampanga - Lacson, Kylene S.; Matuguina, Daisy Mae A.; Cortes, Yna Frances S.; Guinto, Geraldine N.; Caoleng, Clarisse Faye B.; Carlos, Mary Chantelle O. (Future Science / FSH-PH Publications, 2023)
The study aimed to discover the undocumented traditional games within the Municipality of Macabebe, Pampanga, the Philippines. The data findings are to be contextualized in the educational implications of the Physical Education curriculum. With the use of a qualitative research approach, particularly a focused ethnography, a total of 16 key informants with age ranges from 61 to 102 years old participated in the semi-structured interview. After the data process, there were 11 traditional games found, five in the coastal area classified as moderately vigorous intensity when playing while six games in the land were vigorous. Using the Braun and Clarke thematic analysis, three themes were explicated. The first theme encompasses the people in Macabebe’s way of life and how the participants provide basic needs to their families. The second theme describes the origin of undocumented conventional games. The third theme states the educational implications of the Physical Education curriculum among the students. Relatively, the study provides data that enumerates the undocumented traditional games in Macabebe to be integrated into the curriculum.